Acute pneumonitis after subcutaneous injection of BIO-ALCAMID® in breast: Neumonitis aguda secundaria a la inyección subcutánea de gel de polialquilamida (BIO-ALCAMID) en mamas - Villanueva-Villegas, Renzo (2023)
ABSTRACT: Filling materials are used to correct soft tissue deficits. Local and systemic complications are described when these substances are applied. The polyalkylamide gel (Bio-alcamid) used as filler material has been associated with complications at the facial level, while at the pulmonary level they have not been reported in the literature. We present the case of a patient who consulted due to sudden progressive dyspnea hours after the subcutaneous injection of Bio-alcamid in the breasts. After the clinical evaluation and the result of auxiliary tests, the diagnosis of acute pneumonitis secondary to the injection of this substance is concluded. Follow-up of the case was carried out with favorable evolution and resolution of symptoms after three months. We conclude that Bio-alcamid can generate complications at the pulmonary level, therefore, the intervention of public policies that regulate its use, commercialization and application by non-medical personnel is necessary.